The effect of recruitment, selection, training, and job placement on employee performance in Central Jakarta public broadcasting institutions - Ahmad Syarifudin Sukasih; Kamaludin Kamaludin (Jurnal Mantik, 2026)
Public broadcasting organizations need an integrated human resource management system while adapting to the demands of digital broadcasting and public services. At TVRI Headquarters, preliminary institutional records show that 5 of the 18 planned training programs were not implemented, qualification-position mismatches remained in some units, and the selected indicators of commitment and cooperation were below the institutional target. Previous Indonesian studies have generally examined recruitment, selection, training, or placement separately and concentrated in the private sector, leaving limited evidence of their combined effects in public broadcasting. Therefore, this study examines the simultaneous and relative effects of the four practices on employee performance. A cross-sectional explanatory survey was conducted among 114 selected employees with simple random sampling from a population of 158; sample size is determined using the Slovin formula at an error tolerance of 5%. Data were collected using a five-point Likert instrument and analyzed by multiple linear regression at SPSS 26. The results showed that all independent variables, namely recruitment (X1), selection (X2), training (X3), and job placement (X4), had a positive and significant effect on employee performance (Y), both partially and simultaneously. Recruitment contributed 35.7% with a tcal value of 32,168 > ttable 1,982 and a significance of < 0.05. The selection contributed 45.0% with a tally of 9,673 > 1,982 tables. Training accounted for 43.3% with a tally of 9,338 > 1,982 tables. Meanwhile, job placement had an effect of 34.1% with a calculation of 7,705 > table 1,982 which were all significant of ? = 5%. Simultaneously, the four variables were able to explain the variation in employee performance by 62.9%, while 37.1% were influenced by other factors outside the research model. The F test yielded a Fcount of 48,814 > an Ftable of 2,450 with a significance of < 0.05, so H0 was rejected and Ha was accepted. Thus, it can be concluded that recruitment, selection, training, and job placement together have a positive and significant influence on the performance of TVRI Central Jakarta employees. These results show that effective and integrated human resource management is essential in improving employee performance optimally